Innowacyjne rozwiązania banków w zakresie płatności mobilnych w Polsce - Wasiołek, Barbara (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
Social and economic changes in Poland force commercial banks to face new challenges. Fierce international competition forces them to search for new ways of increasing their competitiveness. Flexibility and responsiveness to the rapidly changing needs and expectations of customers seem to be a prerequisite for main- taining the market position and building competitive advantage. This reąuires banks to develop an ability to introduce changes such as innovative financial Solutions. The widespread presence of the Internet combined with dynamie development of payment services opens new possibilities for application of innovations in mobile payments. One of the examples of applying innovative Solutions in the sector of financial services is the launching of the BLIK mobile payments system